Using Audio Visual Screencast-O-Matic Media to Improve Learning Outcomes for PKN Class IV Pkn Students at SDN 05 Botumoito, Boalemo Regency - Fandi H. Binggo; Ismail Adipu (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
This study shows that the learning outcomes of students in the PKN subject are still in the low category. This is indicated by the low learning activity of students at the time of initial observation, with a percentage level of 33.33% of the 24 students. Therefore the researcher took action using the audio-visual screencast-O-matic learning media of diversity material. From the results of research conducted on student learning outcomes, there was an increase of 41.66% in the first cycle of the first meeting, 50% of the first cycle of the second meeting and 62.5% of the first cycle of the third meeting. Whereas in the second cycle of the first meeting the increase in learning outcomes reached 70.83% and in the second cycle the second meeting had increased up to 87.5%. Based on research conducted in cycle I and cycle II, it can be concluded that by using audio-visual screencast-O-matic media, diversity material can improve student learning outcomes in PKN learning in class IV SDN 5 Botumoito, Boalemo Regency, this is in terms of increasing learning outcomes. students from 33.33% rose to 87.5%.